Presence of the Endocannabinoid System in the Inferior Pulvinar of the Vervet Monkey - Catarina Micaelo-Fernandes; Joseph Bouskila; Jean-François Bouchard; Maurice Ptito (Brain Sciences, 2021)
The expression of the endocannabinoid (eCB) system, including cannabinoid receptor type 1 (CB1R) and the cannabinoid synthesizing (NAPE-PLD) and degrading (FAAH) enzymes, has been well-characterized in the retina of rodents and monkeys. More recently, the presence of CB1R was localized throughout the dorsal lateral geniculate nucleus of the thalamus of vervet monkeys. Given that the retina projects also to the pulvinar either via a direct projection or via the superior colliculus, it was reasonable to assume that this system would be present therein. The visual pulvinar, namely the inferior pulvinar (PI) region, was delineated with calbindin immunohistochemical staining. Using Western blots and immunofluorescence, we demonstrated that CB1R, NAPE-PLD and FAAH are expressed in the PI of the vervet monkey. Throughout the PI, CB1R was mainly colocalized with VGLUT2-positive axon terminals in the vicinity of calbindin and parvalbumin-positive neurons. NAPE-PLD and FAAH rather colocalized with calbindin over the somatodendritic compartment of PI neurons. Our results suggest that visual information coming from the retina and entering the PI is modulated by the eCB system on its way to the dorsal visual stream. These results provide insights for understanding the role of eCBs in the modulation of visual thalamic inputs and, hence, visual perception.